C1 inhibitor deficient hereditary angioedema is related to endothelial dysfunction in young adult and middle‐aged patients - Gokce Gul Atay Sensoy; Derya Baykız; İlkim Deniz Toprak; Deniz Eyice Karabacak; Erdem Bektas; Derya Unal; Aslı Gelincik; Semra Demir (Clinical and Translational Allergy, 2025)
Abstract Background Hereditary angioedema (HAE) is a rare, autosomal dominantly inherited disease characterised by mucocutaneous oedema attacks. Vasoactive mediators and the endothelium play an important role in the pathogenesis of HAE. We aimed to evaluate the endothelial dysfunction in HAE. Methods The study included 35 C1 inhibitor deficient (C1‐INH) HAE patients aged 18–50 years old without any risk factor that could cause endothelial dysfunction, and 25 sex‐ and age‐matched healthy controls (HCs). Bilateral carotid intima‐media thickness (CIMT), flow‐mediated dilation (FMD) measurements, and transthoracic echocardiography (ECHO) imaging were performed. Demographic and clinical features of the patients were evaluated. Results The percentage of FMD (FMD [%]) in C1‐INH HAE patients was significantly lower than in the HCs (p < 0.001). There was no significant difference in the CIMT between C1‐INH HAE patients and HCs. In addition, the findings of the ECHO were similar between the groups. C4 and C1 INH levels at diagnosis, gender, age, disease severity, presence of long‐term prophylaxis treatment and attack frequency were not associated with FMD (%), whereas disease duration was correlated with lower FMD (%) (r = −0.480, p = 0.003). Conclusion The present study indicated the presence of structural endothelial dysfunction in C1‐INH HAE in the absence of atherosclerosis. Moreover, the study revealed that endothelial dysfunction was associated with disease duration, irrespective of disease severity. Further studies are required in order to assess mortality and morbidity due to endothelial dysfunction in C1‐INH HAE and to determine the molecular mechanisms underlying endothelial dysfunction in C1‐INH HAE.